Carotid ligation: what happens in the long term?. Issue 8 (August 1986) - Jha, A N; Butler, P; Lye, R H; Fawcitt, R A
Abstract : The authors reviewed a consecutive series of 115 patients who underwent common carotid ligation during the period 1954-1984. Average follow-up was 10 years. Seventy-three (63%) patients presented following a subarachnoid haemorrhage (SAH) and 42 (36%) presented with the mass effect of an unruptured aneurysm. Thirty-nine (34%) patients were lost to follow-up of whom 27 had had a previous SAH. Forty-six (63%) of the 73 patients traced had suffered a SAH and amongst this group, 11 patients (24%) died from a proven or suspected recurrent haemorrhage within 10 years of ligation. The fatal recurrent haemorrhage rate was, therefore, 2.4%/year. Thirty (71%) of the 42 patients who presented with unruptured aneurysms were traced. Seven of these (23%) died: two following haemorrhage, 1 year and 16 years after carotid ligation and three patients died as a direct consequence of carotid ligation. Check angiographic studies were available for 55 patients following carotid ligation, a mean of 8.4 years after the procedure. Thirteen were conventional angiograms and 42 were intravenous angiograms obtained using the digital subtraction technique. Seventy-six per cent of the aneurysms visualised on the initial studies were either smaller or had apparently disappeared. Only four new aneurysms were detected and in two of these instances, the initial angiographic studies had been incomplete. The authors conclude that the annual rate of fatal recurrent haemorrhage from an intracranial aneurysm following common carotid ligation is of a similar magnitude to that of the natural history of conservatively managed ruptured intracranial aneurysms. Moreover, carotid ligation apparently does not prevent haemorrhage from a previously unruptured aneurysm and the procedure appears to carry a significant morbidity and mortality, even in patients with an unruptured aneurysm.